2016
DOI: 10.1016/j.ijso.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sonic hedgehog in patients undergoing orthognathic surgery

Abstract: Purpose Sonic Hedgehog (SHH) is a regulatory protein involved in bone fracture healing. Orthognathic surgery involves surgical osteotomy of the mandible or maxilla to restore the proper anatomic and functional position in patients with dentofacial deformity. The purpose of this study was to analyze SHH local blood serum concentrations after osteotomy to gain further understanding of the molecular regulation of the initial stage of osteotomy healing. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In concordance with our findings, Soliman and colleagues [ 20 ] reported a significant postoperative increase in OPG level among patients who underwent orthognathic surgery, the level of OPG remained high till the six weeks of follow-up. Similarly, Kunisada and colleagues [ 21 ] showed that OPG local serum levels significantly increased time-dependently after osteotomy (P<0.01). Another report demonstrated an increase in TGF-β1 appeared at the later postoperative time and remained at higher levels compared with preoperative levels among patients who underwent orthognathic surgery [ 22 ].…”
Section: Discussionmentioning
confidence: 80%
“…In concordance with our findings, Soliman and colleagues [ 20 ] reported a significant postoperative increase in OPG level among patients who underwent orthognathic surgery, the level of OPG remained high till the six weeks of follow-up. Similarly, Kunisada and colleagues [ 21 ] showed that OPG local serum levels significantly increased time-dependently after osteotomy (P<0.01). Another report demonstrated an increase in TGF-β1 appeared at the later postoperative time and remained at higher levels compared with preoperative levels among patients who underwent orthognathic surgery [ 22 ].…”
Section: Discussionmentioning
confidence: 80%